The effects of a virtual reality treatment program for online gaming addiction. Issue 129 (June 2016) - Park, Sung Yong; Kim, Sun Mi; Roh, Sungwon; Soh, Min-Ah; Lee, Sang Hoon; Kim, Hyungjin; Lee, Young Sik; Han, Doug Hyun
Highlights: We developed a novel virtual reality therapy (VRT) program for online gaming addiction (OGA). We compared the treatment effect of VRT to cognitive behavior therapy for OGA. VRT reduced the severity of OGA, showing effects similar to cognitive behavior therapy. VRT improved the functional connectivity of the cortico-limbic circuit. Abstract: Background and objective: Neuroimaging studies have demonstrated dysfunction in the brain reward circuit in individuals with online gaming addiction (OGA). We hypothesized that virtual reality therapy (VRT) for OGA would improve the functional connectivity (FC) of the cortico-striatal-limbic circuit by stimulating the limbic system. Methods: Twenty-four adults with OGA were randomly assigned to a cognitive behavior therapy (CBT) group or VRT group. Before and after the four-week treatment period, the severity of OGA was evaluated with Young's Internet Addiction Scale (YIAS). Using functional magnetic resonance imaging, the amplitude of low-frequency fluctuation (ALFF) and FC from the posterior cingulate cortex (PCC) seed to other brain areas were evaluated. Twelve casual game users were also recruited and underwent only baseline assessment. Results: After treatment, both CBT and VRT groups showed reductions in YIAS scores. At baseline, the OGA group showed a smaller ALFF within the right middle frontal gyrus and reduced FC in the cortico-striatal-limbic circuit. In the VRT group, connectivity from the PCC seed to the left middle frontal and bilateral temporal lobe increased after VRT. Conclusion: VRT seemed to reduce the severity of OGA, showing effects similar to CBT, and enhanced the balance of the cortico-striatal-limbic circuit.